Microstructure Refinement on Crevice Corrosion of High-Speed Rail Steel U75V Visualized by an In Situ Monitoring System - Wang, Jian; Zhang, Binbin; Xu, Weichen; Zhang, Jie; Yang, Lihui; Peng, Zhongbo; Hou, Baorong (Frontiers in Materials, 2022)
Rail foot covered by a fastener will suffer from crevice corrosion, leading to thinning and localized attack of crevice interior posing a risk of failure. This work investigated crevice corrosion behavior of a typical pearlitic high-speed rail steel U75V, focusing for the first time on the effect of pearlitic microstructure refinement achieved by heat treatment with different cooling rates 2, 5, and 10°C/s. Under anodic polarization, localized dissolved spots presented on the as-received sample, where crevice corrosion mostly initiated from. For cooling rates 2 and 5°C/s, localized dissolved spots were also observed but crevice corrosion was mostly presented as general corrosion instead of from local spots, ascribed to enhanced tendency of uniform dissolution due to microstructure refinement and homogenization. For cooling rate 10°C/s, crevice corrosion expanded flocculently, ascribed to preferential dissolution of pearlitic nodules with entangled cementite due to over refinement. Crevice corrosion was obviously accelerated by microstructure refinement. Cooling rates 5 and 10°C/s led to the fastest and slowest expansion of the corroded area, respectively, while the corrosion depth was just the opposite based on the same amount of metal loss. This work provides important information regarding the effect of pearlitic microstructure refinement on crevice corrosion and introduces a facile method for in situ monitoring of crevice corrosion.